STUDY OF APOPTOSIS IN THE SUBLETHAL DOSE OF PENICILLIC ACID TOXICITY IN BROILER CHICKENS: Pharmaceutical Science-Pathology - N. PAZHANIVEL; C. BALACHANDRAN; B.MURALI; RAJ, G.DHINAKAR; V.BALAKRISHNAN; A.RAJA (International Journal of Life Science and Pharma Research, 2014)
Penicillic acid (PA), a mycotoxin, was originally isolated from the cultures of Penicillium puberulum. The present study was undertaken to study the apoptosis in the sublethal dose of penicillic acid mycotoxicosis in broiler chicken. Eighteen day-old broiler chicks were fed with control diet for the period of three weeks. Subsequently, the birds were randomly distributed to two groups of nine birds each and fed with control and 15 ppm of penicillic toxin diets. Three birds from control and treated groups were sacrificed at 24, 48 and 72 h after treatment in the acute toxicity trial. Similarly, six birds (3 control and 3 penicillic acid–15 ppm) were used for subacute toxicity trial (21 days) and sacrificed to study the apoptosis in the spleen and thymus by using flow cytometric analysis with the Annexin V kit to assess apoptosis and necrosis in splenocytes and thymocytes. This research indicated that peak induction of apoptosis was observed at 24 h treatment of penicillic acid (15 ppm).